Clinical practice-changing trials: the HERA study paradigm. Issue 11 (November 2013) - Zardavas, Dimitrios; Ades, Felipe; de Azambuja, Evandro
Trastuzumab, a humanized anti-HER2 monoclonal antibody targeting the extracellular domain of this oncoprotein, represents the archetype of HER2 blocking agents. Its unprecedented efficacy for HER2-positive metastatic breast cancer (BC) led to its clinical development in the adjuvant setting. The HERceptin Adjuvant (HERA) is one of the pivotal adjuvant trastuzumab trials which proved that this compound can change the natural course of early stage HER2-positive BC. The HERA study led to the registration of trastuzumab for the adjuvant treatment of early HER2-positive BC. This trial randomized more than 5000 patients between 1 and 2 years of trastuzumab and observation after the completion of locoregional therapy and (neo)-adjuvant chemotherapy. Additionally, an abundance of subsequent substudies were conducted, addressing important clinical issues for this patient population. The present review article presents a comprehensive overview of the HERA study and its major contributions to the adjuvant treatment of HER2-positive BC patients. Emphasis is given on the lessons learned from this international collaborative experience and how this can be used as a stepping stone for further improvements in the field.